2021
DOI: 10.1088/1402-4896/ac0273
|View full text |Cite
|
Sign up to set email alerts
|

Decoherence dynamics of a charged particle within a non-demolition type interaction in non-commutative phase-space

Abstract: This paper studies decoherence without dissipation of charged magneto-oscillator in the framework of quantum non-demolition type interaction in non-commutative phase-space. The master equation is derived considering the non-commutativity effects of a bath of harmonic oscillators to study the dynamics of such a system, and its possible exact solution is presented. By analyzing this solution, it turns out that the process involving decoherence without energy dissipation can be observed explicitly. In addition, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…We have studied the decaying dynamics of a displaced harmonic oscillator for initially coherent and squeezed states. (15). The parameters are α = 4, ω = 4, γ = 10, λ = 0.7, r = 0.3, where we choose to maintain the real part r of the squeeze coefficient and variate their complex phase θ.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have studied the decaying dynamics of a displaced harmonic oscillator for initially coherent and squeezed states. (15). The parameters are α = 4, ω = 4, γ = 10, λ = 0.7, r = 0.3, where we choose to maintain the real part r of the squeeze coefficient and variate their complex phase θ.…”
Section: Discussionmentioning
confidence: 99%
“…some time ago, Mandal [14], shows a way to calculate the quasidistribution of photons in the squeezed states of light when the parameters are taken as purely real. Germain et al [15] explicitly shows the effects of a non-commutative bath of oscillators on a magneto-oscillator, they gives the solution for decoherence without dissipation using the master's equation formulation. Recently, Lu [16], reported the evolution of orthogonal coherent states given the solution of the master's equation, showing how the decoherence affects the negativity of the associate Wigner's function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the corresponding study linear entropy has been considered as the measure of the purity of the states in non-commutative space [34]. The density operator and the Wigner function for an an-harmonic oscillator were computed in a 2D non-commutative phase space and the effects of magnetic field on the decoherence rate were highlighted, using time-independent coefficients, featuring the Markovian heat bath dynamics [35][36][37]. Later, the master equation was derived for the momentum coupling scenario in the framework of non-Markovian dynamics [38].…”
Section: Introductionmentioning
confidence: 99%
“…al [3] showed that in a ring arrangement of coupled harmonic oscillators. Decoherence without dissipation of a charged magneto-oscillator by using quantum non-demolition interactions in non-commutative phase-space has also been recently studied [2].…”
Section: Introductionmentioning
confidence: 99%